Deprived social status is associated with decreased use of oral chemotherapy in patients with metastatic colorectal cancer: A retrospective cohort study on administrative databases in a French University Hospital. Issue 6 (12th November 2021) - Gautier, Gwendoline; Lucas, Mélodie; Vermeulin, Thomas; Di Fiore, Frederic; Merle, Veronique
Abstract: Factors associated with the choice of oral versus intravenous CT are not clearly established. Our purpose was to evaluate the influence of social status and home distance to hospital on the use of oral CT in patients with metastatic colorectal cancer (mCRC). This retrospective single‐center study included mCRC patients between 2011 and 2017. Patient social status was assessed by European Deprivation Index (EDI) and home distance to the hospital was calculated. Univariable and multivariable logistic regression analyses were performed. One hundred and seventy‐five mCRC patients were included, with 71 receiving oral CT. Most deprived patients received less oral CT (OR 0.5 [0.26, 0.96], p  = .039). No association was found for road distance. Previous use of adjuvant oral CT was associated with oral CT in mCRC (OR 2.65 [1.06, 6.66], p  = .038). Our results suggest that deprived social status is a factor associated with decreased use of oral CT in patients with mCRC. Clinical trial registration : no registration.